Colossal permittivity with ultra-wide temperature stability in Bi + Ca co-doped BaTiO3 - Tingting Fan; Qi Shi; Wenrong Xiao; Guangzu Zhang; Feng Huang; Wenlin Wang; Wen Dong; Shenglin Jiang; Jing Wang (Journal of Materiomics)
The poor temperature stability of the BaTiO3 ceramic has always been the main problem limiting their application. This situation has been improved but sacrifices the intrinsic polarization, which significantly reduces the dielectric constant. In this work, the mechanism of multiple polarization was creatively introduced, and the temperature stability and dielectric properties of BaTiO3-based ceramics are simultaneously enhanced. In particular, the Ba0.9925Bi0.005Ti0.995Ca0.005O2.995 (BBTC0.5) ceramic sample achieved excellent temperature stability (−14.8% to 8.85%) over an ultra-wide temperature range (−47 to 400 °C) and exhibited colossal permittivity (27,125, 25 °C, 1 kHz) and low dielectric loss (0.07, 25 °C, 1 kHz). The dielectric properties, complex impedance spectra combined with XPS results indicate that the defective dipole clusters (Ti3+-VO..-Ti3+, BiBa. and CaTi″-VO..) along with surface effects lead to colossal permittivity effect. More importantly, SEM images show the presence of the second phase at grain boundaries, which prevent the carriers within the grains from accumulating at the grain boundaries. As a result, the dielectric loss was reduced and the temperature stability was further extended. This strategy breaks the traditional limitation of single/noncomprehensive enhancement by single-polarization mechanism, and is of great theoretical and practical significance to promote the research and application of high-performance BaTiO3-based ceramic materials.